Tindak Kekerasan terhadap Tokoh Perempuan Masa Perang dalam Novel Perawan Remaja dalam Cengkeraman Militer Karya Pramoedya Ananta Toer - Ria Martisa; Nurizzati Nurizzati; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2013)
This study aimed to describe the violence contained in the grip of the novel Virgin Teens Military Pramoedya Ananta Toer. In the grip of the novel Virgin Teens Military Pramoedya Ananta Toer many interesting things to study, especially regarding violence. For that reason, the study of theory in this study included are: the nature of the novel, novel structure, analytical approach to fiction, sociology, literature, violence. This research is descriptive qualitative with research method, content analysis techniques. The data of this research is a form of the language that suggests violence in the novel Virgin Teens in the military's grip Pramoedya Ananta Toer which includes the trace elements based characterizations. The data source of this research is novel in the grip of the military in the Virgin Teens Pramoedya Ananta Toer the Popular Library published by Scholastic in 2001.Data were collected with the following steps: (1) read a novel repetitive elements associated with a mark, (2) inventory data by using invetarisasi format data. Once the data is collected, the data were analyzed using the following steps: (1) classify the data, (2) interpret data (3); interpret the findings and discussion of the existing problems, and (4) write a report based on the findings and discussion .